Advertising and Campaign Props in the Perspective of Enviromental Ethics in West Aceh - Darusman S, Chandra; Basri, Basri; Ath Thariq, Phoenna; Rotin Djusfi, Apri; Fazri, Anhar (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Installation of advertisements and campaign props on trees in West Aceh Regency has begun because the 2024 election campaign. It is suspected to be done because the wider community can easily see them and not require expensive promotional costs. West Aceh Regency Qanun has regulated the provisions prohibiting the installation of symbols, flags, banners, and other attributes in certain places. This study aims to find out and explain the suitability of West Aceh Regency Qanun Number 3 of 2021 with the concept of environmental ethics, find out the basis for exceptions to the installation of advertisements and campaign props on trees can be done with the permission of the Regent and find out how law enforcement against violations of the use of trees as a place to install advertisements and campaign props in West Aceh Regency. This study is an empirical juridical study with a prescriptive method that uses library research as secondary data and field study conducted to obtain primary data through interviews and FGDs with informants. The results show that Article 15, paragraphs (1) and (2) of West Aceh Qanun Number 3 of 2021 still need to follow environmental ethics. Hence, it creates a biased interpretation of whether or not the installation of advertisements and campaign props on tree media certainly impacts the emergence of inconsistencies.